2022
DOI: 10.18016/ksutarimdoga.vi.947387
|View full text |Cite
|
Sign up to set email alerts
|

Afyonkarahisar İlinde Patates Üretiminin Ekonomik Analizi

Abstract: Bu çalışmanın amacı; patates üretimi yapan işletmelerin üretim maliyetlerini ve kârlılık göstergelerini hesaplayarak işletmelerin ekonomik analizini ortaya koymaktır. Çalışma alanı olarak Afyonkarahisar ilinin seçilmesinde Türkiye’nin önemli patates üretim merkezlerinden biri olması etkili olmuştur. Çalışmanın ana materyali 2019 üretim yılında patates üretimi yapan işletmeler arasından tabakalı tesadüfi örnekleme yöntemiyle seçilen 79 işletmeyle görüşülerek elde edilen veriler oluşturmaktadır. İşletmelerde dek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The LR test was calculated as 68.359 and showed an effect of non-random variables in terms of potato production in the enterprises. These results agree with Kadako glua and Karli [27]. Additionally, the lambda (λ) value is greater than one, indicating inefficiency.…”
Section: Technical Inefficiencies Of Potato Enterprisesupporting
confidence: 90%
See 3 more Smart Citations
“…The LR test was calculated as 68.359 and showed an effect of non-random variables in terms of potato production in the enterprises. These results agree with Kadako glua and Karli [27]. Additionally, the lambda (λ) value is greater than one, indicating inefficiency.…”
Section: Technical Inefficiencies Of Potato Enterprisesupporting
confidence: 90%
“…This means that an increase in farm labour affected potato production and the profitability of farmers. These findings are consistent with Rahman [35], Kadako glua nd Karli [27], and Wassihun et al [33], which highlight the adverse effects of increased labour expenditure on production output. However, these results contradict the findings of Dube et al [36], who found a positive contribution of labour to potato production.…”
Section: Profit Efficiency and Inefficiency Estimates Of Potato Enter...supporting
confidence: 88%
See 2 more Smart Citations
“…Most studies estimate technical efficiency using SFA, however, some studies estimate economic, technical, and allocative efficiencies in the agriculture sector of Bangladesh using DEA and SFA [17][18][19][20]. There are several studies on the comparison between DEA and SFA for different crops in different countries [9,[21][22][23][24][25][26][27][28][29][30]. To the best of our knowledge, in the context of Bangladesh, there is a gap in research on potato farming efficiency using both SFA and DEA.…”
Section: Introductionmentioning
confidence: 99%